The multiple exp-function method to obtain soliton solutions of the conformable Date-Jimbo-Kashiwara-Miwa equations - Eidinejad, Zahra; Saadati, Reza; Li, Chenkuan; İnç, Mustafa; Vahidi, Javad (World Scientific Publ Co Pte Ltd, 2024)
Considering the importance of using nonlinear evolution equations in the investigation of many natural phenomena, in this paper, we consider the (2+1)-dimensional Date-Jimbo-Kashiwara-Miwa ((2+1)-dimensional DJKM) equation, we will investigate the solutions for this equation. Using the multiple exp functions method, we obtain analytical solutions for this equation, which are one-soliton, two-soliton and three-soliton solutions and these solutions include three categories of soliton wave solutions, i.e., one-wave solutions, two-wave solutions and three wave solutions. We have performed all calculations with a computer algebra system such as Maple and have also provided a graphical representation of the obtained solutions.
Keywords: ME-function method; soliton wave solutions; conformable Date-Jimbo-Kashiwara- Miwa equations; (2+1)-dimensional D-J-K-M